Spray-gel formulations of Cantigi extract and Cantigi extract-loaded gelatin nanoparticles as antioxidant - Kosasih, Kosasih; Alifiya, Nesshi (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Spray-gel formulations may contain natural antioxidants like plant extracts. They can reduce free radicals and prevent premature aging. This research aims to study spray-gel formulations using Cantigi extracts and Cantigi extract-loaded gelatin nanoparticles as antioxidants. Extract preparation used the maceration method concentrated by a rotavapor and characterized for specific and nonspecific parameters. Antioxidant activity analysis of extract, nanoparticles, and formulations used the DPPH method. Gelatin nanoparticle synthesis was done using the nanoprecipitation method and then characterized for particle size, polydispersity index, zeta potential, entrapment efficiency, aldimine linkage formation, and morphology. Two spray-gel formulations were manufactured (F1 contained the extract, and F2 contained the nanoparticles) and evaluated for one month for organoleptics, homogeneity, viscosity, flow properties, spray pattern, pH, and antioxidant activity tests. The extract and nanoparticles meet all parameters. The antioxidant activities (IC50) are Cantigi extract of 17.4 ppm, gelatin nanoparticles of 33.6 ppm, F1 of 60.6 ppm, and F2 of 99.5 ppm. After the stability study, the spray-gel formulation characteristics were: Organoleptics, homogeneity, homogeneity, and viscosity complied (F1 and F2); flow property showed plastic thixotrophy properties (F1 and F2); spray pattern showed best at 20 cm distance (F1 and F2); pH complied (F1 and F2); and IC50 of F1 was 63.0 ppm while F2 was 103.3 ppm. Conclusions were that the spray-gel formulations (F1 and F2) complied with the standards and were stable during the storage time. However, F1 has more potent antioxidant activity than the F2.